2005
DOI: 10.1097/00001813-200504000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy strategies in the treatment of small cell lung cancer

Abstract: Lung cancer is the most prevalent, yet most preventable malignancy worldwide. Given the tendency of small cell lung cancer (SCLC) to early relapse and its subsequent resistance to treatment, there is an urgent need to optimize standard treatment strategies and develop new treatments. Over the last decade, several strategies have been adopted and advances in the molecular biology of lung cancer have identified a number of targets for future therapy. In this article, we review chemotherapy strategies that have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Increased DNA repair capacity would be anticipated as detrimental to cisplatin efficacy, while decreased DNA repair capacity would result in a more positive initial response to the therapy. Cisplatin is a front-line treatment for a variety of cancers, including testicular, lung and ovarian cancers, as well as tumors of the head and neck [75][76][77][78][79]. The importance of DNA repair capacity in influencing chemosensitivity has been born out in a subset of cancers and treatments.…”
Section: Ner and Response To Chemotherapeuticsmentioning
confidence: 99%
“…Increased DNA repair capacity would be anticipated as detrimental to cisplatin efficacy, while decreased DNA repair capacity would result in a more positive initial response to the therapy. Cisplatin is a front-line treatment for a variety of cancers, including testicular, lung and ovarian cancers, as well as tumors of the head and neck [75][76][77][78][79]. The importance of DNA repair capacity in influencing chemosensitivity has been born out in a subset of cancers and treatments.…”
Section: Ner and Response To Chemotherapeuticsmentioning
confidence: 99%
“…In a small study, the ECb and EC combinations were compared, and the researchers reported the equivalence of the two treatments, although ECb was found to be less toxic 13. A number of studies with paclitaxel as monotherapy or as part of combination regimens have been evaluated with inconsistent results in first- and second-line treatment 14,15…”
Section: Discussionmentioning
confidence: 99%
“…Treatments in the past including oral etoposide, standard-and high-dose regimens have been extensively reviewed by the authors in an earlier publication (Popat and O'Brien, 2005). Combination therapy with EP is considered the standard first-line regimen (Sundstrom et al, 2002), but a randomised Phase III trial failed to prove a definitive survival benefit for EP compared with the cyclophosphamide, doxorubicin and vincristine regimen (CAV) (Roth et al, 1992).…”
Section: Treatment Of Edmentioning
confidence: 99%